2020
DOI: 10.21203/rs.3.rs-18513/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic vagus nerve stimulation for drug-resistant epilepsy may influence fasting blood glucose concentration

Abstract: Background Cervical vagus nerve stimulation (VNS) has been widely accepted as adjunctive therapy for drug-resistant epilepsy and major depression. Its effects on glycemic control in humans were however poorly understood. The aim of our study was to investigate the potential effects of VNS on fasting blood glucose (FBG) in patients with drug-resistant epilepsy. Methods Patients with drug-resistant epilepsy who had received VNS implants at the same hospital were retrospectively studied. Effects on FBG, weight, b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This hyperglycemic response to cervical VNS started almost instantaneously and peak blood glucose levels were observed within less than 30 min (Figure 1 in Meyers et al (2016)). Depending on the stimulation parameters, cervical VNS may also raise blood glucose levels in non‐diabetic humans (Liu et al, 2020; Stauss et al, 2019). We also demonstrated that this hyperglycemic effect of cervical VNS is mediated through afferent vagal nerve fibers projecting to the central nervous system (Meyers et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This hyperglycemic response to cervical VNS started almost instantaneously and peak blood glucose levels were observed within less than 30 min (Figure 1 in Meyers et al (2016)). Depending on the stimulation parameters, cervical VNS may also raise blood glucose levels in non‐diabetic humans (Liu et al, 2020; Stauss et al, 2019). We also demonstrated that this hyperglycemic effect of cervical VNS is mediated through afferent vagal nerve fibers projecting to the central nervous system (Meyers et al, 2016).…”
Section: Introductionmentioning
confidence: 99%